Genetic characterization of Malvi cattle using microsatellite markers - Thakur, S S; Parmar, S N S; Ghosh, C G; Thakur, M S; Sharma, Rakesh; Chaudari, M V (The Indian Journal of Animal Sciences, 2011)
Microsatellite markers offer great potential for genetic comparisons within and between populations. They are the best available molecular tools for characterization of breeds. Microsatellite markers (25) were used to screen 70 Malvi cattle. The mean number of alleles was 9.08 per microsatellite locus with the range of 4 (ILSTS011, ILSTS054) to 18 (CSSM663). The range in the allele size was from 88 bp (CSRM60) to 297 bp (ILSTS006). The microsatellite loci deviated significantly from Hardy-Weinberg equilibrium. Sign test and Wilcox on revealed no Bottleneck in recent past in Malvi population. The mean polymorphic information content was 0.71 ranging from 0.41 to 0.91. The overalls means for observed and expected heterozygosity were 0.54 and 0.75 respectively. The overall observed heterozygosity, PIC and Shannon index values were 0.54, 0.71 and 1.67 indicating high gene diversity. The markers used in the present study were highly informative.